2011
DOI: 10.1016/j.ejphar.2011.09.024
|View full text |Cite
|
Sign up to set email alerts
|

C(5) modified uracil derivatives showing antiproliferative and erythroid differentiation inducing activities on human chronic myelogenous leukemia K562 cells

Abstract: The K562 cell line has been proposed as a useful experimental system to identify anti-tumor compounds acting by inducing terminal erythroid differentiation. K562 cells exhibit a low proportion of hemoglobin-synthesizing cells under standard cell growth conditions, but are able to undergo terminal erythroid differentiation when treated with a variety of anti-tumor compounds. In this paper we report a screening study on a set of different modified C(5) uracil derivatives for the evaluation of their antiprolifera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…K562 cells can be differentiated into erythroid cells, which are marked by the increased expression of embryonic/fetal globin genes, such as ζ-, ε- , and γ-globin genes [24], [34]. It has also been suggested that K562 cells can be differentiated into megakaryocytic lineage with the expression of a surface marker, CD41b [35].…”
Section: Resultsmentioning
confidence: 99%
“…K562 cells can be differentiated into erythroid cells, which are marked by the increased expression of embryonic/fetal globin genes, such as ζ-, ε- , and γ-globin genes [24], [34]. It has also been suggested that K562 cells can be differentiated into megakaryocytic lineage with the expression of a surface marker, CD41b [35].…”
Section: Resultsmentioning
confidence: 99%
“…4). It should be underlined that the level of induction reached in these experimental conditions is even higher than that exhibited by the most powerful inducer described [30].…”
Section: Discussionmentioning
confidence: 68%
“…The level of induction was found to be dose-dependent, all the analyzed globin mRNAs were clearly induced, the level of induction was dramatic for α-globin, ζ-globin and γ-globin mRNA sequences, but clearly evident also for ε-globin mRNA. When the experiment was repeated ( n  = 3) using the highest furocoumarin concentration reproducible results were observed, and if the results were compared to reference K562 cells treated with a control HbF inducer, this induction level was higher than the most effective K562 erythroid inducer available, 1-octylthymine [30]. In fact the induction of ζ-globin mRNA was 48.5-fold ± 8.5 for 4′,5′-DMP, 64.6-fold ± 8.2 for 4,6,4′-TMA and 37-fold ± 6.8 for 1-octylthymine (data not shown and Ref.…”
Section: Resultsmentioning
confidence: 90%
“…K562 cells are also commonly used for the screening of various inhibitors, including Bcr‐Abl kinase inhibitor candidates and antitumor compounds that induce cell differentiation . Differentiation treatment is an advanced strategy for neoplasia therapies and is based on the identification and use of pharmaceutical agents that act as differentiation promoters …”
Section: Introductionmentioning
confidence: 99%